Sri Kehati Stock Index Portfolio Optimization - Deby Indah Mayriska; Hermanto Siregar; Nimmi Zulbainarni (UNIVED Press, 2024)
The purpose of this research is to analyze the composition of stocks to form the optimal portfolio of 25 issuers included in the SRI KEHATI Index for the period 2017 – 2021. The method used to form the portfolio is the Single Index Model (SIM) and the Capital Asset Pricing Model (CAPM), to measure stock performance using the Sharpe, Treynor and Jensen indices and equipped with a Monte Carlo simulation to measure the level of risk (Value at Risk). This research is a descriptive and quantitative research using secondary data. The calculation results show the composition of the portfolio and the proportion of funds: (1) SIM method, there are 5 stocks namely: BBCA (69%), BBRI (13%), EXCL (8%), JPFA (5%) , TINS ( 4%) with portfolio return of 1.49%, Sharpe index 0.16525, Treynor 0.00994, Jensen 0.0178 and the highest VaR value is found at the 99% confidence level in TINS stock , which is -44.3%. (2) CAPM method, there are 8 stocks namely: BBCA (23.59%), BBRI (16.27%), BMRI (16.19%), EXCL (13.95%), BBNI (11.50%), JPFA (7.08%), TINS ( 6.77 %), UNTR (5.56%) with a portfolio return of 0.47%, Sharpe index 0.02298, Treynor 0.00065, Jensen 0.00180 and the highest VaR value is found at a 99% confidence level in TINSstocks , which is - 45.1%.